MARKET AS "THE INVISIBLE HAND" OR STATE INTERVENTIONISM AS "THE VISIBLE HAND" OF ECONOMIC POLICY - Stevanović, Simo; Đorović, Milutin; Milanović, Milan (Economics of Agriculture, 2011)
This paper presents two mutually opposed aspects of the market as a regulatory mechanism in the economy. From the aspect of entrepreneurship, the free operation of "invisible hand" encourage the successful, but limits and neutralizes unsuccessful, and from the aspect of social equality, through the market, legally deepens the gap between rich and poor. It was pointed out that the resolution of decades of controversy of the market as a regulatory mechanism leads to the balanced operation of markets and social equality criteria, which is the one of the characteristics of models of economic systems of developed countries in Europe and the EU. As a way to resolve market controversies, transition countries have adopted the model of "reformed welfare society". The results of transition in Central and Southeastern European countries are different and depending on the closeness of their model of a market economy with developed European countries. The economic effects of the transition were monitored in two groups of countries that became full members and third, those which have not yet. Countries from the first and second group that have became full members of the EU in 2004, according to selected indicators, in 2003 reached or surpassed the pre-transition level of development. From the third group of countries that have not yet joined the EU, Croatia has the best value for most indicators. Measured by purchasing power parity Croatia reached 50% of GDP in EU-25. Unfortunately, analyzed indicators were much lower in Serbia. The value of GDP reached only 30% of the EU-25, and FDI/capita 1119 euros, especially so called "Green field" investments, are at the level of 24.4% of Croats. Analyzed indicators in the third group of countries are well below that level.